Pengaruh Corporate Social Responbility, Capitak Intensity dan Inventory Intensity terhadap Tax Avoidance - Septiani Wulandari; Rusdi Rusdi (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Corporate tax avoidance has become a central issue in financial and sustainability reporting, as stakeholders increasingly expect companies to demonstrate accountability, transparency, and compliance with tax regulations. In the Indonesian property sector, where asset-based activities dominate corporate operations, understanding the factors that influence tax avoidance becomes particularly important. This study examines the effect of Corporate Social Responsibility (CSR), Capital Intensity, and Inventory Intensity on tax avoidance in property companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Employing a quantitative approach and an associative research design, the study utilizes secondary data obtained from annual reports and sustainability reports prepared in accordance with the GRI 2021 standards. The sample was selected through purposive sampling, resulting in six companies with 36 total observations. Data analysis was conducted using panel data regression with the assistance of EViews 12. The findings reveal that CSR disclosure has a positive and significant effect on tax avoidance, indicating that companies with more extensive CSR reporting tend to engage in higher levels of tax avoidance. In contrast, Capital Intensity and Inventory Intensity exhibit no significant effect, suggesting that the proportion of fixed assets and inventory does not substantially drive tax avoidance strategies. These results emphasize the role of non-physical factors such as managerial incentives, governance mechanisms, and regulatory conditions in shaping corporate tax behavior.